Human Development Inequality Inter-regional in Southeast Sulawesi Province 2019–2023 - Herman Lawelai; Elaine Baulete (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The Human Development Index (HDI) is a crucial indicator for measuring the quality of life of a population and the effectiveness of development policies in a region. In Southeast Sulawesi Province, the aggregate HDI has increased from 71.61 in 2019 to 72.94 in 2023. However, this improvement has not been evenly distributed across districts and cities, reflecting spatial disparities in human development. Objective: This study aims to analyze the HDI trends in 17 districts and cities in Southeast Sulawesi over the past five years and to identify patterns of inequality as well as potential influencing factors. Method: A descriptive quantitative approach was employed, utilizing secondary data from the Central Bureau of Statistics (BPS). The analysis was conducted through trend calculations of HDI growth and interregional comparisons based on HDI achievement categories. Results: The findings indicate that the cities of Kendari and Baubau consistently exhibit the highest HDI levels, while regencies such as South Buton and West Muna lag significantly behind. This disparity is influenced by unequal access to basic services, infrastructure development, and the varying economic capacities of local areas. Conclusion: Human development in Southeast Sulawesi demonstrates a positive trend but remains uneven. There is a need for affirmative policy interventions targeting regions with low HDI to promote equitable and sustainable development.